Effectiveness of educational video in improving oral hygiene in preschool students - Adistia, Rinintha; Wafa, Wade'ah; Riyanti, Eriska; Setiawan, Arlette Suzy Puspa Pertiwi (Universitas Padjadjaran, 2020)
Introduction: In recent years, attention has been drawn toward assessing the effectiveness of an oral health education program, especially for preschool students, in order to improve oral hygiene status. There is a difference in the level of ability and learning methods based on age. For early childhood, they tend to imitate the things they see, both people and multimedia images. This research was aimed to analyse the effectiveness of educational video in improving oral hygiene level in preschool students. Methods: This type of research was quasi-experimental with one group pretest-posttest design. The sampling method was the total sampling and obtained 40 subjects. The research population was all students in Al Azhar Kindergarten aged 4-6 years and met the inclusion criteria. Greene and Vermilion Plaque Index was applied to measure the oral hygiene status of each subject before and after the intervention with educational video. The intervention consisted of four meetings; each meeting consisted of before and after plaque index measurement and also after watching the educational video. Data were analysed using t-paired statistical analysis. Results: The result showed a comparison of difference of the plaque index value change on the day I with day VII, which obtained the t-value = 3.365, higher than the t-table = 2.02. Conclusion: Educational video is effective in improving oral hygiene in preschool students by reducing the plaque accumulation.